Demonstration and mental practice in the acquisition of the motor skills - F.S. Fonseca; M.B. Siqueira; A.T. Bruzi; J.V. Fialho; H. Ugrinowitsch; R.N. Benda (Desafio Singular, 2008)
Demonstration and mental practice are variables capable to enhance the learning of motor skills. The purpose of this study was to show the empirical knowledge produced on demonstration and mental practice studies, as well as, a possible relation between these variables effects in the acquisition of motor skills. The results of studies suggest that these variables act similarly in the process of mental representation of the skill, that will be learned. Thus, perhaps the association of demonstration and mental practice can provide an interesting strategy in the acquisition of motor skills.